2001
DOI: 10.1097/00005373-200109000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII for Adjunctive Hemorrhage Control in Trauma

Abstract: The results of this report suggest that in trauma patients rFVIIa may play a role as an adjunctive hemostatic measure, in addition to surgical hemostatic techniques, and provides the motivation for controlled animal and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
1
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(219 citation statements)
references
References 47 publications
3
204
1
11
Order By: Relevance
“…However, the drug has been used in other situations with uncontrolled bleeding, including life-threatening obstetric hemorrhage [49,51,52]. Several case reports and reviews have described decreased blood product requirements in surgical and trauma patients with uncontrolled bleeding with the administration of rFVIIa [53,54]. The mechanism of action of rFVIIa is to augment the intrinsic clotting pathway by binding with tissue factor and directly activating factors IX and X [49,54].…”
Section: Activated Recombinant Factor VIImentioning
confidence: 99%
“…However, the drug has been used in other situations with uncontrolled bleeding, including life-threatening obstetric hemorrhage [49,51,52]. Several case reports and reviews have described decreased blood product requirements in surgical and trauma patients with uncontrolled bleeding with the administration of rFVIIa [53,54]. The mechanism of action of rFVIIa is to augment the intrinsic clotting pathway by binding with tissue factor and directly activating factors IX and X [49,54].…”
Section: Activated Recombinant Factor VIImentioning
confidence: 99%
“…9,10) Conclusion: RFVIIa has been used for about a decade in the treatment of hemophilia patients with inhibitors of coagulation factors VIII and IX, particularly in those undergoing surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown that rFVIIa effectively decreases blood loss at trauma [45] and also increased evidence of its efficacy at trauma patients was found [46,47]. In a multicentre, double-blind, prospective, randomized, placebo-controlled trial rFVIIa was shown to be effective and safe in reducing PRBCs transfusion especially in blunt trauma patients, as well as showing a good safety profile [48] when used as an adjunct to trauma care [49].…”
Section: Optimal Treatment Of Critical Bleeding In Traumamentioning
confidence: 99%
“…In the absence of monitoring of the overall haemostasis, administration of rFVIIa and PCCs is unacceptable. The mechanism of action of rFVIIa suggests enhancement of haemostasis, which is limited to the site of injury without the activation of the coagulation process [47]. Therefore, its use in traumatic haemorrhage is rational.…”
Section: Treatment Of Critical Bleeding After Trauma Between Recommenmentioning
confidence: 99%